2011
DOI: 10.1007/s10384-010-0903-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of a hyperdried cross-linked amniotic membrane as initial therapy for corneal perforations

Abstract: Three cases of corneal perforations were successfully managed using HDCL-AM patching with tissue adhesive. The HDCL-AM was resistant to collagenases during in vitro digestion testing. The HDCL-AM was a useful substrate for corneal perforations. This simple surgical technique may be one of the initial therapeutic options for corneal perforations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…In addition dried AM preparations, cross-linked with glutaraldehyde, have been used as a primary treatment for corneal perforations, indicating its increased usefulness over cryopreserved AM in certain clinical situations[51]. This may reflect easier surgical handling of the dried tissue, which can be glued rather than sutured onto the ocular surface[30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition dried AM preparations, cross-linked with glutaraldehyde, have been used as a primary treatment for corneal perforations, indicating its increased usefulness over cryopreserved AM in certain clinical situations[51]. This may reflect easier surgical handling of the dried tissue, which can be glued rather than sutured onto the ocular surface[30].…”
Section: Discussionmentioning
confidence: 99%
“…AM was used in clinic for many decades for wound healing in burns, promoting epithelium formation and protecting against infection [39, 40]. Recently, the use of AM has been evaluated as a wound dressing material for surgical defects of the oral mucosa [41], ocular surface reconstruction [40, 42], corneal perforations [43, 44], and bladder augmentation [45]. …”
Section: Introductionmentioning
confidence: 99%
“…The hyperdry device and sterilization by γ‐irradiation at 25 kGy, which has been recommended for terminal sterilization of medical products, can completely prevent known transmissible infections, and no adverse effects have been reported in patients who received HD‐AM grafts . Bacteriologic test also indicated that 25 kGy γ‐irradiation achieved to complete sterilization(data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…HD‐AM was also shown to reduce wound dehydration. The details of these benefits are described in clinical observations and case reports …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation